Early South African newspaper reporting of climate change - McCarthy, Jarred Dean (My University, 2019)
Mass media is a medium used for scientific knowledge dissemination, informing society, and therefore shaping society’s perspectives. A highly popularised aspect of scientific discourse in the media is climate change, given its potential threat to livelihoods, the environment, and related political and economic agendas. For the aforementioned reasons, qualitative research was undertaken to examine the diachronic portrayal, and subsequent development, of early climate change by several English South African newspapers, including The Rand Daily Mail and The Star. The undertaking of this research is made possible given an existing newspaper clippings archive at the South African Weather Service, 1906-present. The period under examination, 1906-1956 (50 years), represents significant shifts in environmental, and political agendas. Articles that contained early climate change as their point of interest were further analysed using discourse analysis and thematic content analysis by means of a coding process as well as utilising a narrative analysis. By researching diachronically, it became possible to document and describe the development of early climate change, and the development of the South African media’s technique(s), and process(es) of how early climate change was portrayed. Findings suggest that without Professor Schwarz professing that South Africa was undergoing ‘climatic changes’, a progressive decrease in rainfall, early climate change would not have been covered as extensively as it was throughout the 1906-1955 time period analysed. This debate divided ordinary citizens and experts who agreed with Professor Schwarz and the South African scientific community, who did not agree that a progressive decrease in rainfall was occurring. Results also suggest that journalists played a central and critical role in the development of early climate change and in the development of a scientific consensus thereon. Journalists pushed for clarity on the underlying causes that resulted in ‘climatic changes’, which subsequently expanded the debate to include both anthropogenic and natural facets of early climate change such as solar variability, ENSO and land-use change among others.
Submitted in fulfillment of the requirements for the degree, Master of Science (by dissertation) in Geography and Environmental Studies, in the School of Geography, Archaeology and Environmental Studies, in the Faculty of Science, the University of the Witwatersrand, Johannesburg
Keywords: Climatic changes; Discourse analysis; Mass media